2020
DOI: 10.1016/j.giq.2020.101521
|View full text |Cite
|
Sign up to set email alerts
|

User roles for emergency management in social media: Understanding actors' behavior during the 2018 Majorca Island flash floods

Abstract: Social media assemble multiple users' interactions across singular events. Authorities need to navigate this diversity to effectively communicate and promote collaborative strategies. During emergency situations, discerning “who is there” is even more important for authorities, as this tracing process can save lives reaching the appropriate targets. This article contributes to this problem during emergency situations by proposing a user role taxonomy. We argue that focusing on functional behaviors could bypass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 40 publications
0
12
0
3
Order By: Relevance
“…Social media platforms provide government agencies with a channel to reach citizens immediately, inform citizens of the crisis conditions, contain the spread of false information, respond to stakeholder requests, monitor the situation, and help victims. Previous studies have reported many cases of government use of social media in different kinds of crises such as earthquakes (Zhang et al, 2020 ), floods (Villodre & Criado, 2020 ), nuclear disasters (Utz et al, 2013 ), water pollution (Yuan & Gascó, 2018 ), smog (Lin et al, 2016 ), and riots (Panagiotopoulos et al, 2014 ). These studies mainly focused on the timeliness (Spence et al, 2015 ; Wukich, 2016 ; Yuan & Gascó, 2018 ), the content (Chen et al, 2020 ; Wang et al, 2021 ), and the dissemination features (Kim & Hastak, 2018 ; Wukich et al, 2019 ) of government social media use during crises.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Social media platforms provide government agencies with a channel to reach citizens immediately, inform citizens of the crisis conditions, contain the spread of false information, respond to stakeholder requests, monitor the situation, and help victims. Previous studies have reported many cases of government use of social media in different kinds of crises such as earthquakes (Zhang et al, 2020 ), floods (Villodre & Criado, 2020 ), nuclear disasters (Utz et al, 2013 ), water pollution (Yuan & Gascó, 2018 ), smog (Lin et al, 2016 ), and riots (Panagiotopoulos et al, 2014 ). These studies mainly focused on the timeliness (Spence et al, 2015 ; Wukich, 2016 ; Yuan & Gascó, 2018 ), the content (Chen et al, 2020 ; Wang et al, 2021 ), and the dissemination features (Kim & Hastak, 2018 ; Wukich et al, 2019 ) of government social media use during crises.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Usage of social networking sites and digital technologies provides the general population with appropriate and effective means of disseminating and consuming information [30]. Throughout natural or man-made disasters, millions of people are rapidly turning to social media to disclose information [31,32].…”
Section: Artificial Intelligence and Disaster Managementmentioning
confidence: 99%
“…En general, la investigación sobre redes sociales en las administraciones deberá enfrentarse a ciertos desafíos para reducir algunas de sus lagunas. En primer lugar, los académicos deben comenzar a prestar más atención al estudio de los actores que se relacionan con las administraciones (Villodre y Criado, 2020b;Panagiotopoulos et al, 2017). Sin mejorar la comprensión sobre quiénes son esos actores podemos tener dificultades para comprender cómo deben dirigirse los mensajes, y, en definitiva, para entender y mejorar la conformación de la identidad digital de cada administración.…”
Section: Líneas De Investigación Y Métodosunclassified
“…Sin mejorar la comprensión sobre quiénes son esos actores podemos tener dificultades para comprender cómo deben dirigirse los mensajes, y, en definitiva, para entender y mejorar la conformación de la identidad digital de cada administración. En ese sentido, analizar el comportamiento de esos actores puede ayudar a académicos y administraciones públicas a comprender mejor sus comunidades y cómo actúan ante ciertos eventos (Villodre y Criado, 2020b;Shwartz-Asher et al, 2017). En segundo lugar, el gran interés que han suscitado los estudios centrados en la dimensión externa de las redes sociales ha eclipsado el desarrollo del conocimiento sobre el uso que hacen los empleados públicos de estas tecnologías para relacionarse profesionalmente (Criado et al, 2019;Demircioglu y Chen, 2019;.…”
Section: Líneas De Investigación Y Métodosunclassified